2021
DOI: 10.1371/journal.pntd.0009318
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasmosis in the Republic of Congo dominated by African histoplasmosis, Histoplasma capsulatum var. duboisii

Abstract: The Republic of Congo (RoC) is one of the African countries with the most histoplasmosis cases reported. This review summarizes the current status regarding epidemiology, diagnostic tools, and treatment of histoplasmosis in the RoC. A computerized search was performed from online databases Medline, PubMed, HINARI, and Google Scholar to collect literature on histoplasmosis in the RoC. We found 57 cases of histoplasmosis diagnosed between 1954 and 2019, corresponding to an incidence rate of 1–3 cases each year w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The true burden of histoplasmosis is currently unknown, and adequate mapping is lacking. There is a need to probably institute active localized surveillance programs in endemic areas, particularly in previously suggested epicenters in Transvaal and Cape Province, South Africa [ 35 ], Kimpese, Democratic Republic of the Congo [ 18 ], Ogbunike, Nigeria [ 35 ], and Brazzaville, Republic of Congo [ 99 ], and rural areas with potentially high risks. Nearly all cases of histoplasmosis reported in the literature are diagnosed in tertiary medical centers in urban cities, and patients sometimes need to travel long distances.…”
Section: Resultsmentioning
confidence: 99%
“…The true burden of histoplasmosis is currently unknown, and adequate mapping is lacking. There is a need to probably institute active localized surveillance programs in endemic areas, particularly in previously suggested epicenters in Transvaal and Cape Province, South Africa [ 35 ], Kimpese, Democratic Republic of the Congo [ 18 ], Ogbunike, Nigeria [ 35 ], and Brazzaville, Republic of Congo [ 99 ], and rural areas with potentially high risks. Nearly all cases of histoplasmosis reported in the literature are diagnosed in tertiary medical centers in urban cities, and patients sometimes need to travel long distances.…”
Section: Resultsmentioning
confidence: 99%
“…Our review seems to indicate that there is an underreporting of paediatric histoplasmosis from Africa (only 6% of the cases). Two recent reviews focusing on African histoplasmosis reported that 25% and 30% of the 57 and 94 cases, respectively, were children [95,96]. Lack of awareness and clinical recognition, as well as a lack of management resources, might well explain this observation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a case series study by Pakasa et al 9 revealed a high incidence (44.4%, 16/36) of histoplasmosis in young children, within the age range of 3–7 years. In a more recent review by Amona et al , 10 of the 54 cases reported in Congo, 17 (31.5%) were from the pediatric age group. However, there still exist occurrences of histoplasmosis being misdiagnosed as other clinical conditions like tuberculosis (TB), pneumonia, cancers, nephrotic syndrome and hyperreactive malarial splenomegaly syndrome.…”
Section: Introductionmentioning
confidence: 93%